Divergence and estimates of genetic parameters in Crambe abyssinica: an oilseed plant for industrial uses - de Oliveira, Rebeca Lourenço; Dias, Luiz Antônio dos Santos; Corrêa, Thais Roseli; Ferreira, Pedro Henrique Silva; da Silva, Martha Freire (Revista Ceres, 2018)
Crambe’s breeding is still incipient, with few cultivars of interest. The aims of the present study were: i) to evaluate the divergence between 10 genotypes of crambe, through morphoagronomic and quality traits, using multivariate analyses; and ii) to estimate genetic parameters related to these traits. The trial was conducted in a greenhouse, and the experimental data were submitted to multivariate analysis and genetic evaluation. The genotypes differed significantly among them for plant height (PH), stem diameter (SD), number of branches per plant (NB), height of the first productive branch (HPB), mass of 1000 grains (M1000), grain (PROD) and oil productivities (OIL). The experimental coefficient of variation revealed good precision (4.29 to 13.81%). The averages of PROD (1936.94 kg/ha) and OIL (660.10 kg/ha) were high. The traits presented high estimates of broad-sense heritability on a mean genotype basis (h2>73.65). The cluster analysis revealed five clusters of genotypes. PROD showed the greatest contribution (22.31%) to the diversity among the genotypes, followed by HPB, NB and SD. Genotypes 2 and 4 can be used as parents at future crosses, as they are promising in obtaining segregant populations.